Multilingual cognition and language use - Filipoví, Luna
Includes bibliographical references and indexes.; This volume provides a multifaceted view of certain key themes in multilingualism research today and offers future directions for this research area in the context of the multilingual development of individuals and societies. The selection of studied languages is eclectic. This collection also illustrates novel insights into the linguistic relativity debate that multilingual studies can offer, such as new and revealing perspectives on some well-known topics